Ethnographic exploration of empowerment to improve elderly residents' quality of life - Seyed Zia Tabatabaei; Fatemeh Ebrahimi; Azimi Bin Hj Hamzah; Mohsen Rezaeian; Mahnaz Akbari Kamrani (Wolters Kluwer Medknow Publications, 2017)
Background: Evidence underscores that empowerment is central to improve the elderly residents' quality of life. In truth, empowerment is a process through which individuals gain better control over their life. The aim of this study was to explore how perceived empowerment influence on the quality of life among elderly Malay residents. Materials and Methods: A focus ethnographic approach was employed in a Malaysian residential home between May 2011 and January 2012. Data were gathered from participant observations, field notes, in-depth interviews, and exploring related documents. Results: The analysis of the data gathered in the current study resulted in the development of three themes - social life and its requirements, caregivers' skills empowerment, and listening and supporting. Conclusions: Findings of the study provide new insights that are useful in charting new guideline for care providers and policy makers to improve the elderly residents' quality of life.